Hiking Sport Tourism Development at Mount Papandayan: A Qualitative Assessment Using the MSPDM Framework - Zakia, Rizka; Alif, Muhammad Nur; Fauzi, Rizal Ahmad (Physical Education, Health and Recreation Study Program, Universitas Insan Budi Utomo, Indonesia, 2026)
This study examines the development of hiking sport tourism in high-risk environments by analyzing the interaction between marketability, sustainability, participation, and disaster mitigation within a single analytical framework. Mount Papandayan in Garut Regency was selected as a case study due to its characteristics as an active volcanic destination with high visitor demand and inherent environmental risks. Using a qualitative case study design, data were collected through observation, in-depth interviews, and document analysis involving key stakeholders, including destination managers, government representatives, local communities, and tourists. The findings indicate that while Mount Papandayan demonstrates strong marketability supported by its natural attractions and accessibility, its development is constrained by fragmented governance across key dimensions. Sustainability practices remain largely operational without formalized regulatory mechanisms; community participation is evident but primarily limited to operational roles; and disaster mitigation tends to emphasize reactive response rather than proactive preparedness. These results highlight a structural misalignment between tourism development and governance systems, suggesting that natural attractiveness alone is insufficient to ensure destination competitiveness in high-risk environments. This study contributes by applying the MSPDM framework as an integrative approach to reveal governance gaps and provide context-specific insights, without aiming for broad generalization.